Differential Impacts Of Isokinetic Training On Proprioceptive Active Repositioning Errors Committed By Osteoarthritis Patients - Naresh Bhaskar, Raj; Choo Morley, Liza; Soumendra, Saha; Amran, Ahmed (2018)
The purpose of the present study was to investigate the role of Conventional Physiotherapy (CP), Isokinetic Exercise Training (IET) and combined intervention (CI) of CP and IET in improving proprioception in participants with knee osteoarthritis (OA). 54 post-menopausal female participants in the age range of 45-65 years with knee OA of Grade II severity were recruited from the Orthopaedics Dept. of Hospital Universiti Sains Malaysia (USM). Baseline assessment on the participants were done in the Skill Laboratory of School of Medical Sciences and the Exercise and Sports science laboratory, USM. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used to evaluate the subjective scale for pain, stiffness and physical function. Proprioception was assessed employing the isokinetic device BIODEX 4 System Pro. Thereafter participants were randomly classified into three groups (Gr.) (Viz. Gr. A, Gr. B and Gr. C, with n = 18/group). Gr. A participants received CP comprising of strengthening exercises; stretching exercises and range of motion (ROM) exercises. Gr. B received IET at velocities of 90° and 150°/sec. Gr. C participants received CI, with uniform protocol (25 - 30 min.s/ session; 2 sessions/week for 12 weeks). Mid-term evaluation was done after 6th week followed by the post intervention evaluation after 12th week following preintervention analyses protocol. Two-way repeated measure of ANOVA revealed effectiveness of the interventions in improving proprioception of knee joint in participants with OA of knee joint. IET was better effective in augmenting proprioception involving muscular sense, while CI was observed to facilitate in enhanced proprioception in ligament. Multiple linear regression analyses revealed the association between pain, level of stiffness and physical function with weight, height and level of proprioception.